The association between learning styles, time management skills and pharmacology academic performance among first year medical students in Universiti Putra Malaysia (UPM) during the Covid-19 pandemic - Saat, Azmah; Mohd. Thani, Suryati; Salihan, Safuraa; Ab. Razak, Nur Izah; Masrudin, Siti Saleha (Universiti Putra Malaysia, 2022)
Introduction: The scientific understanding gained from pharmacology investigations is used to support a wide range of medical therapies. As a result, pharmacology is essential in medicine. As a result of the coronavirus epidemic, several colleges throughout the world have resorted to online pharmacology learning, which has an indirect impact on student academic progress. Aside from learning styles, a student’s time management abilities are another essential aspect that affects their academic success. Methods: This is a cross-sectional study that employed a questionnaire to assess first-year medical students from Universiti Putra Malaysia’s Faculty of Medicine and Health Sciences’ learning style and time management skills. A series of pharmacological questions involving short answer questions was also given to the students to assess their pharmacology performance. Results: There was a significant weak negative correlation between superficial learning style and pharmacology performance (r=-0.272, p<.05). There was also a significant weak correlation between deep learning style and long range planning (r=0.256, p<.05) and including short range planning (r=0.263, p<0.5). Lastly, significant weak negative correlation on pharmacology performance and long range planning was seen (r=0.256, p<.05). However, there was no significant correlation between time management and pharmacology performance. Conclusion: Students that use a superficial learning style struggle in school, yet deep learning styles in both short and long term planning do not always increase pharmacology performance. A good time management skills does not guarantee a good pharmacology performance either. Other relevant factors, like as socio-demographic characteristics, that may contribute to this outcome, particularly during this epidemic, should be investigated further.